2019
DOI: 10.1111/ggi.13714
|View full text |Cite
|
Sign up to set email alerts
|

Older adults are prioritized in terms of waiting time under the emergency triage system in Guangzhou, China

Abstract: Aim To assess whether elderly patients are prioritized under the emergency triage system in Guangzhou, China. Methods This was a cross‐sectional survey of clinical data from adult visitors to the emergency department of the Third Affiliated Hospital of Sun Yat‐sen University between 1 August 2015 and 31 December 2017. The primary end‐point was receiving the first medical service within the target waiting time, which varied according to the triage level of the patient. Multivariate logistic regression was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…In three French hospitals, Casalino et al showed that older age was a predictor of longer length of ED stay in unadjusted analyses, but not after adjusting for arrival mode and acuity level [ 31 ]. In contrast, older adults were prioritised and less likely to exceed waiting times in ED in China [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In three French hospitals, Casalino et al showed that older age was a predictor of longer length of ED stay in unadjusted analyses, but not after adjusting for arrival mode and acuity level [ 31 ]. In contrast, older adults were prioritised and less likely to exceed waiting times in ED in China [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This target was then revised but remained as a reference in clinical practice and scientific literature [ 26 , 27 ]. A few studies showed that older adults had an increased risk of exceeding recommended targets [ 26 28 ], while others showed that they were prioritised and seen within target times, after adjusting for triage categories [ 29 , 30 ]. A French study found that age was no longer associated with length of ED stay after adjustment for covariates [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK setting, older patients wait longer, and have a prolonged stay in the ED compared to younger patients [1]. However, there may be some international variation in wait times experienced by older adults [44,45]. As such, it is important that a PREM aimed at older adults examines the experience of waiting, which may give locally relevant insights into where improvement would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain the long time to arrive at hospital among Jordanian older adults with ACS who prefer to use and access transportation services. It took approximately 17 minutes for the participating older adult patients to receive care at the ED, which may be considered a short waiting time as compared to the waiting times reported among older adult patients with ACS symptoms in studies conducted prior to the COVID-19 pandemic (Garofalo et al, 2012; Pan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%